Minimal Local Analgesic Dose of Intrathecal Bupivacaine and Ropivacaine in Patients Undergoing Cesarean Section: A Comparative Study - Singh, Jeevan; Shrestha, Ashish; Kharbuja, Kalpana; Tandukar, Alex; Shrestha, Abha (Journal of Lumbini Medical College, 2019)
Introduction: Spinal anesthesia is considered a reasonable option for cesarean section. Bupivacaine and ropivacaine have been used as intrathecal drugs alone or in combination with various opioids. Ropivacaine is considered a valid and safe alternative to bupivacaine for intrathecal anesthesia. This study aims to determine the median effective dose (ED50) of intrathecal bupivacaine and ropivacaine for cesarean section and defines this as the minimum local anesthetic dose (MLAD).Methods: Forty pregnant women undergoing elective cesarean section were allocated and randomized into two groups. The initial dose was 13mg for both ropivacaine and bupivacaine groups and was increased or decreased of 0.3mg, using the up-down sequential allocation technique. Efficacy was accepted if adequate sensory dermatomal anesthesia to pinprick to T6 was attained within 20 minutes after intrathecal injection and required no supplemental epidural injection for procedure until at least 50 minutes after the intrathecal injection of test drugs. The MLAD for both bupivacaine and ropivacaine was calculated with 95% confidence interval using the formula of Dixon and Massey. Comparison of different variables between the groups was done using t-test with significant p value at < 0.05.Results: The two groups were comparable in terms of demographic profile and clinical characteristics. The MLAD of ropivacaine and bupivacaine were 11.63 mg (95% CI, 11.5-12.92) and 10.459 mg (95% CI, 10.12-10.87) respectively. The potency ratio between spinal ropivacaine and bupivacaine was 0.89.Conclusion: Ropivacaine provided clinically surgical anaesthesia of shorter duration without compromising neonatal outcome and can be used as a safe alternative to bupivacaine.DOI: https://doi.org/10.22502/jlmc.v7i1.250